Impact of periodontal status on oral health-related quality of life in patients with and without type 2 diabetes. Issue 5 (May 2015) - Irani, F.C.; Wassall, R.R.; Preshaw, P.M.
Abstract Objectives To investigate the impact of periodontal status on oral health-related quality of life (OHRQoL) in patients with and without type 2 diabetes mellitus (T2DM). Methods 61 patients with T2DM and 74 non-diabetic patients matched for age, gender and periodontal status (health, gingivitis, chronic periodontitis) were recruited. The oral health impact profile (OHIP)-49 was self-completed by all participants at baseline and by the patients with periodontitis at 3 months and 6 months after non-surgical periodontal therapy. Results There were no significant differences in the overall OHIP-49 summary scores between patients with T2DM (median; interquartile range; 37.0; 19.5–61.0) and without T2DM (30.4; 16.8–51.0) (p > 0.05). Among non-diabetic patients, there were significantly higher OHIP-49 scores (indicating poorer OHRQoL) in patients with gingivitis (41.0; 19.7–75.7) and periodontitis (33.0; 19.9–52.5) compared to patients who were periodontally healthy (11.1; 7.1–34.5) (p < 0.05), though such an effect was not observed in the patients with diabetes. In the non-diabetic patients with periodontitis, statistically significant reductions in OHIP-49 scores were noted in the psychological discomfort and psychological disability domains following periodontal treatment, indicating an improvement in OHRQoL. In contrast, there were no statistically significant changes in OHIP-49 scores following periodontal treatment in the patients with diabetes. Conclusion T2DM does not impact on overall OHRQoL as measured by OHIP-49. Chronic periodontitis and gingivitis were associated with poorer OHRQoL in non-diabetic patients, with evidence of improvements following periodontal treatment, but no such effects were observed in patients with diabetes. Clinical significance Gingivitis and periodontitis are associated with reduced OHRQoL compared to periodontal health in non-diabetic patients, with improvements following treatment of periodontitis. No impact of type 2 diabetes on OHRQoL was noted; this may be related to the burden of chronic disease (diabetes) minimising the impact of oral health issues on OHRQoL.